Heart-Failing Jehovah's Witness Patient Successfully Treated by Minimally Invasive LVAD Implantation without Any Blood Transfusions - Hanke, Jasmin S.; Avsar, Murat; Haverich, Axel; Schmitto, Jan D. (The Thoracic and Cardiovascular Surgeon Reports, 2015)
Left ventricular assist device (LVAD) implantation without the use of any blood products is considered as a challenge. We present a 48-year-old patient (175 cm, 75 kg, body mass index 24.5 kg/m2) who was admitted to our clinic due to end-stage heart failure. The patient is a Jehovah's witness. He declined full blood transfusion as well as use of coagulation factors. Therefore, we interdisciplinary decided to implant an LVAD via minimally invasive technique. The patient experienced an uneventful intrahospital stay and was successfully discharged home on his 17th postoperative day, proving that LVAD implantation without blood transfusions is possible by using a minimally invasive technique. This benefits not only Jehovah's witness patients, but also all patients in need of an LVAD.
Keywords: minimally invasive; LVAD; left ventricular assist device; Jehovah's witness